Identification of Visual Character of Leaves with Sumatran Rhino's Urine in the Sumatran Rhino Sanctuary Way Kambas National Park as Potential Source of eDNA - Priyambodo, Priyambodo; Putri, Chicka R.P.; Rustiati, Elly L.; Kurniawati, Yeyen; Zulkarnain, Danisworo; Pratiwi, Dian N.; Arsan, Zulfi; Giyono, Giyono; Mustikawati, Ganis; Pertiwi, Vindo R.; Sukatmoko, Sukatmoko; Srihanto, Eko A.; Saswiyanti, Enny (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2023)
The sumatran rhinoceros is one of the large endemic mammals to the island of Sumatra, with critically endangered status by the IUCN. Currently, the existence of the sumatran rhino is challenging to find in its natural habitat. Therefore, it is necessary to develop indirect monitoring to maintain and increase the stability of the population in nature. Monitoring through camera traps has been used in several locations. Another method is carried out by identifying traces and remains of the sumatran rhino in natural habitats, for example, through urine samples. The sumatran rhinoceros has the behavior of urinating, namely through urine spray. Urine sprayed by the sumatran rhino will hit plant parts in its habitat, including leaves. This study was aimed to identify the visual characteristics of leaves containing samples of sumatran rhino urination as a potential source of eDNA material. The results showed the leaves characteristics containing the sumatran rhino's urine on the 0, 1, and 2 days after the sumatran rhino urination. The difference in visual observations of the sumatran rhino's urine spray attached to the leaves can be seen through the change in the color of the urine fluid, which is getting more and more concentrated. Visualization of leaves containing sumatran rhino urine can be used to recommend visual leaf characteristics that can be taken as similar samples in natural habitats.